2020
DOI: 10.21273/hortsci15177-20
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Growth, Yield, and Root Development, Soil Nitrogen and Water Distribution as Affected by Nitrogen and Irrigation Rates on a Florida Sandy Soil

Abstract: Effective nutrient and irrigation management practices are critical for optimum growth and yield in open-field fresh-market tomato production. Although nutrient and irrigation management practices have been well-studied for tomato production in Florida, more studies of the current highly efficient production systems would be considered essential. Therefore, a two-season (Fall 2016 and Spring 2017) study was conducted in Immokalee, FL, to evaluate the effects of the nitrogen (N) rates under different irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The root-to-shoot ratio exhibits a different trend because of the negative correlation between root growth and soil moisture level up to a certain point, after which all plant parts, including shoots and roots, fall apart. These findings are in line with those of Chai et al (2016); Singh and Kamal (2012); Ayankojo et al (2020);Al-Selwey et al (2021); Alhashimi et al (2023).…”
Section: Tomato Plants' Vegetative Measurementssupporting
confidence: 90%
“…The root-to-shoot ratio exhibits a different trend because of the negative correlation between root growth and soil moisture level up to a certain point, after which all plant parts, including shoots and roots, fall apart. These findings are in line with those of Chai et al (2016); Singh and Kamal (2012); Ayankojo et al (2020);Al-Selwey et al (2021); Alhashimi et al (2023).…”
Section: Tomato Plants' Vegetative Measurementssupporting
confidence: 90%
“…Here, soil physicochemical properties were altered after fumigation of apple replant soil. Ammonium nitrogen and nitrate nitrogen are the main forms of nitrogen in soil (Ayankojo et al, 2020). These nitrogen forms can be transformed by nitri cation and denitri cation, and nitri cation is one of the most important processes of soil nitrogen transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Badr et al [44] found the same results in tomato plants cultivated with drip irrigation, with WUE being greater at the highest N rate. Similarly, in tomato plants cultivated in the open-field in fall, iWUE was lower (21.88 kg m −3 ) with 134 kg ha -1 N, due to a lower yield, compared with that occurring with application rates of 179-269 kg ha -1 N (29.83-32.85 kg m −3 ); nevertheless, in spring there were no significant differences [45]. Optimizing N supplies is very important in order to improve NUE.…”
Section: Discussionmentioning
confidence: 85%